Factors influencing the choice of information sources among blind and visually impaired community / Tengku Rafidatul Akma Tengku Razali - Tengku Razali, Tengku Rafidatul Akma (2016)
The purpose of this study is to identify the choice of information source among Blind and Visually Impaired Community (BVIC) and develop a new model of Blind and Visually Impaired Community's Choice of Information Sources (BVIC's CIS) by tested the relationship between identified factors from the past research which are information need (functional need and experiential need), information quality, personality (agreeableness, conscientiousness, extraversion, neurotic and openness), relationalism (affection and receptivity) and cost towards choice of information source among BVIC to fill the gap in the current literature. This study was conducted by using the questionnaire and data were collected through a phone call. 268 respondents were selected randomly from the 889 BVIC population from the list name. This study used a structure equation modeling by using the SmartPLS. The finding of this study revealed that main information source among the BVIC was human and followed by the printed source and electronic source. Only functional need, experiential need, agreeableness, extraversion, affection and receptivity have a significant relationship with the BVI's CIS while information quality, conscientiousness, neurotic, openness and cost do not. Hence further research need to conducted in order to understand more on this community because with the new knowledge gained on the associations among the variables, the librarian and other information providers can focus their effort to understanding the BVIC's choice of information sources and provide better information source based on the information need, information quality, personality, relationalism and cost. It is anticipated that this study will contribute towards sustainability development for a better living of the blind and visually impaired community in Malaysia.